The effect of mild to moderate knee osteoarthritis on gait and three-dimensional biomechanical alterations - Pan, Jing; Xie, Zhonghao; Shen, Huifang; Huang, Zhiguan; Zhang, Xiaohui; Liao, Bagen (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundKnee Osteoarthritis (KOA) is a prevalent chronic degenerative joint disease, particularly among the elderly, leading to pain, stiffness, and diminished functionality. The progression of KOA is often associated with significant changes in gait and biomechanics, yet detailed investigations of these changes—especially in early to moderate stages—remain limited. This study aims to conduct a comparative analysis of three-dimensional gait biomechanics in patients with mild to moderate KOA, in order to gain deeper insights into the early biomechanical changes associated with KOA.MethodsA case-control study design was employed, consisting of three groups: Kellgren-Lawrence (K-L) grade I KOA patients, K-L grade II KOA patients, and healthy controls, with 15 participants in each group. Kinetic and kinematic data were collected using two force plates and a three-dimensional motion capture system. Gait parameters, joint range of motion (ROM), angular velocities, and joint moments were analyzed, with a significance level of p < 0.05.ResultsGrade II KOA patients showed prolonged gait cycles, wider step widths, and reduced swing phases on the affected side compared to grade I patients and controls. Grade I patients had reduced hip and knee ROM compared to controls. In the sagittal plane, grade II patients had more significant reductions in knee and ankle ROM. In the coronal plane, grade II patients had less hip and ankle ROM than grade I and controls. Horizontally, grade II patients had greater hip ROM but reduced knee ROM compared to grade I. Additionally, grade I patients showed smaller extension moments in the hip and knee than controls. Grade II patients had lower angular velocities and reduced extension and flexion moments in the hip and knee compared to controls.ConclusionKOA induces significant biomechanical alterations in gait, which become more pronounced with advancing disease severity. These changes highlight the importance of early detection and tailored rehabilitation strategies to improve mobility and prevent further joint degeneration. Understanding the biomechanical profile of KOA at different stages is essential for developing personalized therapeutic approaches aimed at enhancing patient quality of life and reducing the societal burden of KOA.